Triterpene Acids from Euscaphis japonica and Assessment of Their Cytotoxic and Anti-NO Activities - Zhang, Li-Jie; Cheng, Jing-Jy; Liao, Chia-Ching; Cheng, Hui-Ling; Huang, Hung-Tse; Kuo, Li-Ming Yang; Kuo, Yao-Haur (Planta Medica, 2012)
Six new triterpenoids, euscaphic acids G–L (1–6), along with nine known triterpene acids, and two known lignans were isolated from the ethanolic extract of the twigs of Euscaphis japonica. This is the first report concerning 1α,3β-dihydroxy-12-oleanen-28-oic acid isolated from a natural source. The structures of the new compounds were established by spectroscopic analysis. The cytotoxic and anti-NO production activities for the isolates are also evaluated and discussed; compound 1, hederagenin (11), and arjunic acid (12) showed significant cytotoxicity against NCI-H460 cells, HT-29 cells, and CEM cells (IC50 = 1.64 ± 0.87, 2.11 ± 1.54, 1.73 ± 0.64 µM, respectively). Some of the isolated triterpenoids showed marginal inhibitions on NO production induced by LPS.
Keywords: Euscaphis japonica; Staphyleaceae; euscaphic acids G–L; triterpenoids; cytotoxicity; anti-NO production